Role of Interventional Radiology in the Management of Venous Trauma - Kumari, Divya; Kwak, Daniel H.; Fergus, Jonathan (Seminars in Interventional Radiology, 2022)
Traumatic injury to the large, central venous vasculature, although rare, is associated with high morbidity and mortality rates. Conventional open surgical treatment by repair or ligation can be technically challenging in anatomically difficult areas to expose. Furthermore, open surgical approach can release tension on the venous injury and result in uncontrollable bleeding. Endovascular techniques such as stenting and embolization can be used effectively for the treatment of traumatic venous injury. This article will discuss the morbidity and mortality associated with traumatic venous injuries, venous anatomy, endovascular treatment options, and management of traumatic venous injury.
Keywords: venous trauma; stenting; hemorrhage; interventional radiology